An evaluation of crash pads in short track speed skating - Maw, S.; Wong, E.; Kitchen, A.; Oetelaar, T.; Veer, C.; Saunders, T.; Johnston, C.
The aim of this research was to test all conventional variations on short track crash pads used in Canada, and evaluate impact performance with respect to bounce back (velocity), and to peak deceleration and to develop recommendations based on the results.